De amore: Sócrates y Alcibíades en el Banquete de Platón - Rojas, Lorena (2011)
“De amore: Socrates and Alcibiades in Plato’s Symposium”. This articleproposes to study the relationship between Socrates and Alcibiades according toPlato’s Symposium. By these means, we seek to relect upon the other kind of lovewhich Socrates also exempliies in the dialogue, with the aim of understandingSocrates’ behavior towards Alcibiades beyond the moral contraposition betweenthe spiritual love of contemplation and the earthly love of Alcibiades. Moreover,we aim to present an approach to this relationship without identifying it with aSocratic conirmation of Diotima’s version. To this end, we will not neglect theimportant homoerotic atmosphere of the dialogue and the epoch.